The Construction of a 47-Region Inter-regional Input-Output Table, and Inter-regional Interdependence Analysis at Prefecture Level in Japan - Yoshifumi Ishikawa; Toshihiko Miyagi (European Regional Science Association (ERSA), 2004)
In Japan, We can use many input-output tables for regional economic analysis. However, Most of them are not inter-regional input-output tables but intra-regional input-output tables. Therefore, these do not enable analysis in consideration of interregional interdependence except for a famous nine regions covering the whole of Japan by MITI etc. In this study, we attempted to estimate a 47 region-interregional input-output table at the prefecture level covering the whole of Japan. The hybrid approach of constructing regional input-output tables was adopted in this 47 region-interregional input-output study. First of all, all intra-regional input-output tables at prefecture level were prepared. We can use intra-regional input-output tables of all prefectures in Japan from 1990. The second step is the estimation of interregional trade coefficients. When inter-regional input-output tables are constructed, Estimation of interregional trade coefficients is very important. In this study, we propose a method for estimation of interregional trade using a distribution census and some data. And the interregional trade coefficients were adjusted by using a new iterative method so that the sum total of the total output of 47 regions might suit the amount of total output of Japan. Finally, a 47 interregional input-output table was compiled using tables of 47 all prefectures and the interregional trade coefficients. And also, this paper presents some regional economic analysis using a 47 region-interregional input-output table. We can observe the relation between transportation network and inter-regional economic linkage at prefecture level.
Keywords: 330